Versatile synthesis of end-reactive polyrotaxanes applicable to fabrication of supramolecular biomaterials - Tamura, Atsushi; Tonegawa, Asato; Arisaka, Yoshinori; Yui, Nobuhiko (Beilstein Journal of Organic Chemistry, 2016)
Cyclodextrin (CD)-threaded polyrotaxanes (PRXs) with reactive functional groups at the terminals of the axle polymers are attractive candidates for the design of supramolecular materials. Herein, we describe a novel and simple synthetic method for end-reactive PRXs using bis(2-amino-3-phenylpropyl) poly(ethylene glycol) (PEG-Ph-NH2) as an axle polymer and commercially available 4-substituted benzoic acids as capping reagents. The terminal 2-amino-3-phenylpropyl groups of PEG-Ph-NH2 block the dethreading of the α-CDs after capping with 4-substituted benzoic acids. By this method, two series of azide group-terminated polyrotaxanes (benzylazide: PRX-Bn-N3, phenylazide: PRX-Ph-N3,) were synthesized for functionalization via click reactions. The PRX-Bn-N3 and PRX-Ph-N3 reacted quickly and efficiently with p-(tert-butyl)phenylacetylene via copper-catalyzed click reactions. Additionally, the terminal azide groups of the PRX-Bn-N3 could be modified with dibenzylcyclooctyne (DBCO)-conjugated fluorescent molecules via a copper-free click reaction; this fluorescently labeled PRX was utilized for intracellular fluorescence imaging. The method of synthesizing end-reactive PRXs described herein is simple and versatile for the design of diverse functional PRXs and can be applied to the fabrication of PRX-based supramolecular biomaterials.
Keywords: azide group; biomaterials; click chemistry; cyclodextrin; polyrotaxane